2022
DOI: 10.1159/000526104
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Hyperuricemia and Admission Lactate Increases the Risk of Acute Kidney Injury in Patients with ST-Segment Elevation Myocardial Infarction

Abstract: Background and Objective: Acute kidney injury (AKI) is a common complication associated with adverse outcomes among patients with ST-segment elevation myocardial infarction (STEMI). This is conflicting information about the relationship between hyperuricemia and AKI in STEMI. This work aims to investigate the effect of the interaction between hyperuricemia and lactate on the risk of AKI. Methods: We analyzed 2,008 consecutive STEMI patients between January 2014 and January 2019. Hyperuricemia was defined as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Uric acid is produced in the liver and is primarily eliminated by the kidneys. Kidney damage and cardiovascular disease have both been linked to hyperuricemia, according to studies [21]. An independent predictor of the development of microalbuminuria was baseline serum uric acid, according to a prospective cohort study with 1862 participants who did not have the condition [22].…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is produced in the liver and is primarily eliminated by the kidneys. Kidney damage and cardiovascular disease have both been linked to hyperuricemia, according to studies [21]. An independent predictor of the development of microalbuminuria was baseline serum uric acid, according to a prospective cohort study with 1862 participants who did not have the condition [22].…”
Section: Discussionmentioning
confidence: 99%
“…These combined benefits of exercise contribute to lower UA levels and decreased risk of gout attacks. However, it's worth noting that intense exercise may potentially reduce UA solubility by elevating lactate concentration [63], induce dehydrated HU [64], and increase the risk of rhabdomyolysis through the release of UA from skeletal muscle [65]. Therefore, consulting a healthcare professional before starting an exercise regimen is advised, especially for those with medical conditions.…”
Section: Role Of Lifestyle Factorsmentioning
confidence: 99%
“…Elevated uric acid also contributes to the development of complications in STEMI patients. He et al observed a strong correlation between hyperuricemia and the risk of acute kidney injury in STEMI patients [ 39 ]. Also hyperuricemia was associated with CAD serious complications such as post-infarction ventricular arrhythmias, no-/slow-reflow phenomenon, and heart failure [ [40] , [41] , [42] ].…”
Section: The Correlation Between Hyperuricemia and Cadmentioning
confidence: 99%